The origin of diarrhea in rotavirus infection - Stanifer, Megan; Boulant, Steeve (Science, 2020)
Messengers from rotavirus-infected cells induce pathogenic signaling in neighboring cells - Messengers from rotavirus-infected cells induce pathogenic signaling in neighboring cells
Gesehen am 04.05.2021